Fabrication of calcium doped PlSZT ceramics using high planetary mill method - Tuan Ab Rashid, T.N.I.; Mohamad, H.; Ahmad, Z.A; Mohamed, J.J (IOP Publishing Ltd, 2018)
Ca-doped modified lead Lanthanum Strontium Zirconium Titanate (PLSZT) ceramic, was synthesized with different concentrations of dopant in order to enhance the properties of PZT. Calcium carbonate, CaCO3 have been used as a source of Ca dopant in the preparation of PCLSZT using high planetary ball mill, palletized and sintered at 1200 ºC for 3 hours. The uses of high planetary milling benefit in shorten the time for powder preparation where the calcination was not required. The concentration of CaCO3 was varied from 0.01, 0.03, 0.05 and 0.10 mol% and their effects on phase formation, surface morphology, density and porosity have been studied using X-ray diffraction (XRD) and Scanning electron microscopy (SEM). XRD results showed that all Ca-doped PLSZT samples present a tetragonal phase. Whereas SEM results showed that the grain size of the samples was increased with increasing calcium concentration. In addition, the density was observed to be decreased with increasing amount of Ca concentrations.